Embryology - Updates and Highlights on Classic Topics 2012
DOI: 10.5772/35847
|View full text |Cite
|
Sign up to set email alerts
|

The Epididymis: Embryology, Structure, Function And Its Role In Fertilization And Infertility

Abstract: Embryology is a branch of science concerned with the morphological aspects of organismal development. The genomic and molecular revolution of the second half of the 20th century, together with the classic descriptive aspects of this science have allowed greater integration in our understanding of many developmental events. Through such integration, modern embryology seeks to provide practical knowledge that can be applied to assisted reproduction, stem cell therapy, birth defects, fetal surgery and other field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 60 publications
(151 reference statements)
1
33
0
10
Order By: Relevance
“…However, the number of narrow cells in the total epithelial cell population increases along the epididymis from 3% in the initial segment to 6% in the corpus epididymis (Arrotéia et al, 2012). In addition, each cell type in the epididymal epithelium has different roles that influence overall epididymal functions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the number of narrow cells in the total epithelial cell population increases along the epididymis from 3% in the initial segment to 6% in the corpus epididymis (Arrotéia et al, 2012). In addition, each cell type in the epididymal epithelium has different roles that influence overall epididymal functions.…”
Section: Introductionmentioning
confidence: 99%
“…During embryonic development, under the influence of androgens secreted from the male gonad, the Wolffian ducts develop into a number of male reproductive organs, such as the epididymis, vas deferens, and seminal vesicles (Hannema and Hughes, 2007). In general, the differentiation of epididymal epithelial cells appears in two developmental phases during postnatal development a first phase in the early neonatal period, in which halo cells appear from undifferentiated cells, and a second phase, in which there is a sequential differentiation of other cell types until adulthood (Arrotéia et al, 2012). It is believed that a number of lumicrine factors produced by the testis, such as androgens, growth factors, and other secretory molecules, play important roles in the differentiation of the epithelium (Hinton et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These Cxs include Cx26, Cx30.3,Cx31,Cx31.1,Cx32,Cx37,Cx40,Cx43,and Cx45. Comparison analyses of Cx genes expression between the head and tail part of the epididymis from 7 to 91 days of postnatal age conducted by Dufresne et al (2003) demonstrated segmental-specific and postnatal age-differentiated expression patterns of Cx genes in the epididymis. The epididymis is divided into an initial segment (IS), caput epididymis (head), corpus epididymis (body), and cauda epididymis (tail) based on morphological and functional aspects (Arrotéia et al, 2012). Because the head of the epididymis used in Dufresne's research includes the IS, caput epididymis, and corpus epididymis, it is difficult to determine whether their findings truly represent segmentspecific expression of Cx genes.…”
Section: Introductionmentioning
confidence: 99%